Problematika Relawan: Pendampingan Spiritualitas dan Religiusitas Kristen Anak Difabel Kristen - Chrisnatalia, Desy; Damanik, Evalina Chrisna; Ariyanto , Rudy; Wenardy, Anastasia; Tannia, Mellen (INKLUSI, 2022)
The limitation of children with disabilities raises the idea of the barriers of the church and church members in developing spiritual and religious environments. This paper portrays an exploratory study that explores the perceptions of companions or volunteers on the spirituality and religiosity of Christian children with disabilities. Data were collected by focus group discussions among five participants. The finding shows that the mentoring process needs to be criticized, which links the spirituality and religiosity of children with disabilities to praying and singing hymns. The church has not fully implemented inclusiveness both in physical facilities and services. Families have an essential role in developing the spirituality and religiosity of children with disabilities. Characteristics of children more or less hinder the companion in facilitating the development of spirituality and religiosity of children with disabilities. Keterbatasan anak penyandang disabilitas memunculkan gagasan tentang hambatan gereja dan anggota gereja dalam mengembangkan lingkungan spiritual dan keagamaan. Tulisan ini menggambarkan sebuah studi eksplorasi yang menggali persepsi pendamping atau relawan terhadap spiritualitas dan religiusitas anak-anak penyandang disabilitas Kristen. Data dikumpulkan dengan diskusi kelompok terfokus di antara lima peserta. Temuan menunjukkan bahwa proses pendampingan perlu dikritisi, yang mengaitkan spiritualitas dan religiusitas anak difabel dengan berdoa dan menyanyikan lagu-lagu pujian. Gereja belum sepenuhnya menerapkan inklusivitas baik dalam fasilitas fisik ataupun pelayanan. Keluarga memiliki peran penting dalam mengembangkan spiritualitas dan religiusitas anak berkebutuhan khusus. Karakteristik anak sedikit banyak menghambat pendamping dalam memfasilitasi perkembangan spiritualitas dan religiusitas anak dengan disabilitas.